Strangling speculation: The effect of the 1903 Viennese futures trading ban - Laura Wurm (Queen's University Centre for Economic History (QUCEH), 2021)
How does futures trading affect spot price volatility? This paper uses a unique early-twentieth century natural experiment to test what happens when futures trading no longer exists. In 1903, futures trading in the Viennese grain market was banned. The permanency of this ban makes it ideal for studying its effect on volatility, using a difference-in-difference framework. Prices from Budapest, a market operating under similar conditions but unaffected by the ban, are used as a control. This paper finds increased spot price volatility and lower pricing accuracy because the information-transmission and risk-allocation functions of the futures market were no longer maintained.
Keywords: N23; G13; G14; G18; G41; E65; 330; futures trading; volatility; information; market regulation; speculation; commodity markets; agricultural economics; Austro-Hungarian Empire